2012
DOI: 10.3857/roj.2012.30.2.62
|View full text |Cite
|
Sign up to set email alerts
|

Treatment outcome of conservative surgery plus postoperative radiotherapy for extremity soft tissue sarcoma

Abstract: PurposeTo evaluate the treatment outcome and prognostic factor of postoperative radiotherapy for extremity soft tissue sarcoma (STS).Materials and MethodsForty three patients with extremity STS were treated with conservative surgery and postoperative radiotherapy from January 1981 to December 2010 at Korea University Medical Center. Median total 60 Gy (range, 50 to 74.4 Gy) of radiation was delivered and 7 patients were treated with chemotherapy.ResultsThe median follow-up period was 70 months (range, 5 to 302… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 18 publications
2
13
1
Order By: Relevance
“…Regarding the prognosis of secondary malignancy, contrary to previous reports showing that the prognosis of osteosarcoma as an secondary malignancy was poorer than that of primary osteosarcoma [1,20,28], our results showed that its prognosis may not be inferior. Lee et al [21] reported that the 2-year overall survival and eventfree survival rates of patients with osteosarcoma as a secondary malignancy were 56% and 33%, respectively.…”
Section: Survival and Recurrencecontrasting
confidence: 99%
“…Regarding the prognosis of secondary malignancy, contrary to previous reports showing that the prognosis of osteosarcoma as an secondary malignancy was poorer than that of primary osteosarcoma [1,20,28], our results showed that its prognosis may not be inferior. Lee et al [21] reported that the 2-year overall survival and eventfree survival rates of patients with osteosarcoma as a secondary malignancy were 56% and 33%, respectively.…”
Section: Survival and Recurrencecontrasting
confidence: 99%
“…This might be at least partly attributable to the use of neoadjuvant chemotherapy, although major responses according to RECIST criteria were rare. Further on, local control seemed to be at least slightly improved compared to recent series using EBRT alone (pre-or postoperatively), which reported consistently 5-year-LC rates of 83-93% [6,[19][20][21][22][23][24][25][26] with mainly comparable R1-resection rates (0-25%) as in our trial. This might be attributable to the increased biological effect of the high single dose which was guided directly to the high risk region under visual control via IOERT, but given the limited number of patients in our study and the lack of a control arm, it cannot be ruled out that this difference has occurred by selection bias or randomly.…”
Section: Discussionsupporting
confidence: 62%
“…However, these treatments often have adverse effects or are ineffective, e.g., for retroperitoneal sarcomas the 5-year local control rate is only 40–71% and the 5-year survival rate is low with 51–60% [ 5 ]. Sarcomas of the extremities have a high local recurrence rate of 30–50% and half the patients die from their disease [ 6 ].…”
Section: Introductionmentioning
confidence: 99%